Keberterimaan dalam Keberagaman: Refleksi Pendidikan Budaya dalam Pesantren - Eizza Afkarina; Imam Bukhori (LP3M Universitas Islam Zainul Hasan Genggong, 2020)
Pesantren has flourished long before the formal educational institutions established in Indonesia. Thus, it has great contribution to the development of this nation. Pesantren as Indonesian indigenous educational system plays important role in enculturation process to shape the positive qualities of culture among generation to generation. As the islamic religius educational institution, it is administrated by kyai as the central figure who has high religius esoteric knowledge and standard of moral and ethics. In pesantren, santri has been taught to rcognise the values of plurality, equality, tolerance and hold in high esteem of humanity based on the basic teaching and ideas of ahlus sunnah wal jama’ah paradigm. And as a sub-culture, pesantren also has firm bearing with local and indonesian culture. It means that pesantren has to formulate itself to civilize the locals as its real potention to maintain the indonesian noble culture.